2021
DOI: 10.3390/jof7110971
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nile Blue Analogue Stains Yeast Vacuolar Membrane, Endoplasmic Reticulum, and Lipid Droplets, Inducing Cell Death through Vacuole Membrane Permeabilization

Abstract: Phenoxazine derivatives such as Nile Blue analogues are assumed to be increasingly relevant in cell biology due to their fluorescence staining capabilities and antifungal and anticancer activities. However, the mechanisms underlying their effects remain poorly elucidated. Using S. cerevisiae as a eukaryotic model, we found that BaP1, a novel 5- and 9-N-substituted benzo[a]phenoxazine synthesized in our laboratory, when used in low concentrations, accumulates and stains the vacuolar membrane and the endoplasmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 66 publications
3
5
0
Order By: Relevance
“…This incubation resulted in the accumulation of the compounds in the cells, as NIR fluorescence emission was observed for all compounds upon excitation (Figure 1). Looking closely at Figure 1, it can be observed that these compounds appear to accumulate particularly at the vacuolar membrane and/or at the perinuclear membrane of the endoplasmic reticulum, which is consistent with our previous observations for this class of compounds [23,35,36]. In fact, Compounds 3a and 3b have a high specific labeling for the vacuole membrane and perinuclear membrane of the endoplasmic reticulum.…”
Section: Fluorescence Microscopy Studies 241 General Observationssupporting
confidence: 90%
See 2 more Smart Citations
“…This incubation resulted in the accumulation of the compounds in the cells, as NIR fluorescence emission was observed for all compounds upon excitation (Figure 1). Looking closely at Figure 1, it can be observed that these compounds appear to accumulate particularly at the vacuolar membrane and/or at the perinuclear membrane of the endoplasmic reticulum, which is consistent with our previous observations for this class of compounds [23,35,36]. In fact, Compounds 3a and 3b have a high specific labeling for the vacuole membrane and perinuclear membrane of the endoplasmic reticulum.…”
Section: Fluorescence Microscopy Studies 241 General Observationssupporting
confidence: 90%
“…To confirm our previous observations and to evaluate the fluorescence pattern of each compound individually, we analyzed the specific intracellular distribution of the compounds using S. cerevisiae cells expressing GFP-tagged proteins located at the vacuole (W303-1A Vba1-GFP-expressing a GFP-tagged form of the vacuole membrane transporter Vba1 [56]), at the endoplasmic reticulum (BY4741 Sec66-GFP-expressing a GFP-tagged non-essential subunit of Sec63 ER complex [57]) and at the plasma membrane (23344c jen1∆ Jen1-GFP-expressing a GFP-tagged functional lactate transporter Jen1 [58]). We also reduced the concentration of the compounds and stained the cells with 2.5 µM of 3a-f, as we had previously observed that this concentration increased the specificity and labeling ability of the compounds of this family [35]. As previously reported, reducing the concentration of the compounds proved to be beneficial for live-cell imaging experiments.…”
Section: Vacuole Perinuclear Membrane Of the Endoplasmic Reticulum An...mentioning
confidence: 88%
See 1 more Smart Citation
“…In our previous work, we used the yeast Saccharomyces cerevisiae as a eukaryotic cell model and performed a detailed characterization of the effect of one of our most active compounds, BaP1 (Figure 1). We found that BaP1 accumulates in the vacuole, the yeast lysosome equivalent organelle, and induced a regulated cell death process associated with vacuolar membrane permeabilization [23].…”
Section: Introductionmentioning
confidence: 90%
“…However, this class of compounds has shown to possess antiproliferative activity, which has increased the interest in evaluating them as pharmaceutical drugs. In fact, there are several reports of different activities for these compounds, such as antifungal [22][23][24][25], antimalarial [26,27], antibacterial [28,29], antiviral [30], and antitumor [31,32]. Still, despite the interest, the information available regarding their mechanisms of action is still limited.…”
Section: Introductionmentioning
confidence: 99%